Global Trends of Stem Cell Precision Medicine Research (2018–2022): A Bibliometric Analysis - Liu, Muge; Yang, Fan; Xu, Yingbin (Frontiers in Surgery, 2022)
Background Stem cells are a group of cells that can self-renew and have multiple differentiation capabilities. Shinya Yamanaka first discovered a method to convert somatic cells into pluripotent stem cells in 2006. Stem cell therapy can be summarized into three aspects (regenerative treatment, therapy targeted at stem cells, and establishment of disease models). Disease models are mainly established by induced pluripotent stem cells, and the research of stem cell precision medicine has been promising in recent years. Based on the construction of 3D, patient-specific disease models from pluripotent induced stem cells, proper research on disease development and treatment prognosis can be realized. Bibliometric analysis is an efficient way to quickly understand global trends and hotspots in this field. Methods A literature search of stem cell precision medicine research from 2018 to 2022 was carried out using the Web of Science Core Collection.VOSviewer, R-bibliometrix, and CiteSpace software programs were employed to perform the bibliometric analysis. Results A total of 552 publications were retrieved from 2018 to 2022. Annual publication outputs trended upward and reached a peak of 172 in 2021. The United States contributed the most publications (160, 29.0%) to the field, followed by China (63, 11.4%) and Italy (60, 10.9%). International academic collaborations were active. CANCERS was considered the most productive journal with 18 documents. NATURE was the most co-cited journal with 1860 times citations. The most cited document was entitled “Induced Pluripotent Stem Cells for Cardiovascular Disease Modeling and Precision Medicine: A Scientific Statement From the American Heart Association” with 9 times local citations. “ precision medicine” (n = 89, 12.64%), “personalized medicine” (n = 72, 10.23%), “stem cells” (n = 43, 4.40%), and “induced pluripotent stem cells” (n = 41, 5.82%), “cancer stem cells” (n = 31, 4%), “organoids” (n = 26, 3.69%) were the top 6 frequent keywords. Conclusion The present study performs a comprehensive investigation concerning stem cell precision medicine (2018–2022) for the first time. This research field is developing, and a deeper exploration of 3D patient-specific organoid disease models is worth more research in the future.